The Many Shades of Bilingualism: Language Experiences Modulate Adaptations in Brain Structure. (20th December 2019) - Pliatsikas, Christos; DeLuca, Vincent; Voits, Toms
Abstract: Recent years have seen an expansion in the research related to structural brain adaptations related to the acquisition and processing of additional languages. However, the accumulating evidence remains to a great extent inconsistent, with a large variety of cortical, subcortical, and cerebellar effects reported in various studies. Here we propose that the variability in the data can be explained by the differences in the language background and experiences of the tested samples. We also propose that the field should move away from monolithic bilingual versus monolingual comparisons; instead, it should focus on the experiences of the bilingual groups as predictors of structural changes in the brain, and also employ longitudinal designs to test the dynamic effects of active bilingualism. The implications of the proposed approaches for the suggested benefits of bilingualism on ageing and patient populations are also discussed. Abstract :